Correlation between creatine kinase and match load in soccer: a case report - De Albuquerque Freire, L.; Tannure, M.; Gonçalves, D.; Aedo-Muñoz, E.; Vanenzuela Perez, D. I.; Brito, C. J.; Miarka, B. (Journal of Physical Education and Sport, 2020)
Our study evaluated the correlation of data measured by GPS (in the strength, endurance, and speed stimulus divisions) and creatine kinase (CK) levels in professional soccer players after a match. For this purpose, the sample was composed by 123 measures of the same 24 players who stayed at least 75-min on the field, during five professional matches. The measures were taken in two periods: a) 24 hours (CK-T1) and b) 48 hours (CK-T2). The main results indicated that there was a positive correlation between CK-T1 and displacement% above 14 km/h (19%±5%; p=0.029) and% above 18 km/h (8%±2.9%; p=0.048), efforts above 18 km/h (58.6%±20.3%; p=0.04), decelerations (35.6±10.4 frequencies; p=0.004), explosive efforts (126.9±37.4 frequency; p=0.004) and inverse correlation with minutes of effort (91.9±9.8 frequency/min; p=0.016). For the CK-T2 there was a positive correlation with accelerations (31.3±9.2 frequency; p=0.009), decelerations (35.6±10.4 frequency; p=0.008), explosive efforts (126.9±37.4 frequency; p=0.004), inverse correlation with the total load (895.1±143.3 index; p=0.008) and minutes of effort (91.9±9.8 frequency/min; p=0.014). Our data indicate that the use of GPS can directly infer the degree of muscle damage, suppressing invasive measures that can lower the cost of the sport.